Chinese Affixes and Word Formation - Fu Ruomei (Humaniora, 2014)
Chinese language is one of the typical isolated languages. It lacks morphological variation; part of speech has no morphological signs; the additional component of word formation is less; and the roots never change their forms. The major method of Chinese word formation is the combination of roots according to certain grammatical relations. Although the affix word formation is not part of mainstream Chinese word formation, affix-formation is still an integral part of the Chinese word-formation. Article used literature review, summarized the types and meanings of Chinese affixes. And meanwhile, article analyzed word formation function of Chinese Affixes and quasi-affixes. The Chinese quasi-affixes have stronger capabilities in forming new words, but development direction of Chinese quasi-affixes has to stand the test of time.